A rare case of cervical tuberculosis mimicking carcinoma cervix - Singh, Sanjay; Seth, Atul; Basu, Ipsita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Cervical tuberculosis is a rare entity with only limited number of case reports in the literature. A 53 year old, P1, post-menopausal housewife presented with history of one episode of post-menopausal bleeding and whitish discharge per vaginum. Speculum examination revealed an ulceroproliferative cervical growth. Clinically she was diagnosed to have carcinoma cervix. However, cervical biopsy confirmed the diagnosis of cervical tuberculosis. She was treated with anti-tubercular drugs for six months and has been disease free for the last two years. This case emphasizes the fact that though cervical tuberculosis is rare, it should be considered in the differential diagnosis of carcinoma cervix.